If f(x)=3x-2 and g(x)=2x+1 find (f-g)(x)

Question

If f(x)=3x-2 and g(x)=2x+1 find (f-g)(x)

in progress 0
Orla Orla 2 months 2021-07-21T12:26:02+00:00 1 Answers 1 views 0

Answers ( )

    0
    2021-07-21T12:27:50+00:00

    9514 1404 393

    Answer:

      (f-g)(x) = x -3

    Step-by-step explanation:

      (f-g)(x) = f(x) -g(x)

      = (3x -2) -(2x +1)

      = 3x -2 -2x -1 = (3x -2x) +(-2 -1)

      (f-g)(x) = x -3

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )